2010
DOI: 10.1002/micr.20784
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, hemodynamical and hemorheological changes of mature artificial saphenous arterio‐venous shunts in the rat model

Abstract: Artificial femoral arterio-venous (AV) shunts are widely used in rodent models for studying shunt maturation and to optimize various surgical techniques. However, little is known about complex circulatory, microcirculatory, and hemorheological effects of end-to-side saphenous AV shunts. We aimed to study these parameters in mature AV shunts. Studying these questions in CD rats, end-to-side anastomoses were made between the left saphenous artery and vein. On the right-side the nonoperated saphenous vessels serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Mortality rates in fistula studies have generally ranged between 0 and 47% [16, 22-24]. Most of the deaths occur 24–48 h after surgery, because of congestive heart failure (CHF) or for unknown reasons [16, 22, 25]. No postoperative deaths and no infections were observed in the current study.…”
Section: Discussionmentioning
confidence: 67%
“…Mortality rates in fistula studies have generally ranged between 0 and 47% [16, 22-24]. Most of the deaths occur 24–48 h after surgery, because of congestive heart failure (CHF) or for unknown reasons [16, 22, 25]. No postoperative deaths and no infections were observed in the current study.…”
Section: Discussionmentioning
confidence: 67%
“…Concerning the follow-up of morphological and functional changes of artificial shunts, in a previous work we demonstrated significant hemodynamic and notable microrheological (red blood cell deformability and aggregation) alterations in case of artificial sapheno-saphenous arterio-venous shunt model in the rat 44 . In a recent study, we found aorto-portacaval differences in the certain hemorheological parameters (red blood cell aggregation, erythrocyte elongation index, osmotic gradient ektacytometry parameters) 45 .…”
Section: Intraoperative Microcirculatory Investigationsmentioning
confidence: 79%
“…The majority of data referring to arterio-venous or porto-caval micro-rheological differences are originated from experimental studies, which deal with ischemia-reperfusion of limbs [15,26,30], small intestine [7], liver [10], cerebral hypo-and hyperperfusion [18,25] and artificial arterio-venous shunt models [14]. However, there is a lack of targeted comparative hemorheological analysis for exploring these arterio-venous or porto-caval micro-rheological relations.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,14,15,18,19,25,26]. The small volume of required blood sample for these laboratory tests (microliter-amount) and the sophisticated methodology provided the opportunity for further investigation of arterio-venosus micro-rheological differences in laboratory animals [13,14,29], or as laboratory standardization concerns, the systemic venous versus capillary blood samples in human [28]. The standardization of blood sampling methods and sites are important for the experimental surgical and microsurgical research models, too.…”
Section: Introductionmentioning
confidence: 99%